2008
DOI: 10.1038/ijir.2008.41
|View full text |Cite
|
Sign up to set email alerts
|

ISA, ISSAM, EAU, EAA and ASA recommendations: Investigation, treatment and monitoring of late-onset hypogonadism in males

Abstract: The new ISA, ISSAM, EAU, EAA and ASA recommendations on the investigation, treatment and monitoring of late-onset hypogonadism in males provide updated evidence-based information for clinicians who diagnose and treat patients with adult onset, age related testosterone deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
167
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(175 citation statements)
references
References 89 publications
6
167
0
2
Order By: Relevance
“…[1][2][3] Low testosterone levels have been linked to a variety of symptoms such as reduced muscle mass, low bone mineral density, impairment of libido, sexual performance, well-being and cognitive function and an increase of mood disorders. [4][5][6] Although data regarding the effect of androgens on somatic parameters, such as bone mineral density or lean body mass, are quite robust, the effect of late-onset hypogonadism for the genesis of reduced 'cognitive function' or 'mood disorders' is poorly understood. The potential association is of considerable interest as depression and Alzheimer dementia (AD) belong to the most prevalent diseases in aging western populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Low testosterone levels have been linked to a variety of symptoms such as reduced muscle mass, low bone mineral density, impairment of libido, sexual performance, well-being and cognitive function and an increase of mood disorders. [4][5][6] Although data regarding the effect of androgens on somatic parameters, such as bone mineral density or lean body mass, are quite robust, the effect of late-onset hypogonadism for the genesis of reduced 'cognitive function' or 'mood disorders' is poorly understood. The potential association is of considerable interest as depression and Alzheimer dementia (AD) belong to the most prevalent diseases in aging western populations.…”
Section: Introductionmentioning
confidence: 99%
“…A consistent relationship between testosterone and dehydroepiandrosterone sulfate (DHEAS) levels on the one hand and depression and AD on the other has not been sufficiently supported. 5 We therefore analyzed the association between depression and AD to total testosterone and DHEAS serum levels in aging men. All men were participants of the Vienna Transdanube Aging (VITA) study, which is a longitudinal, population-based study of men all aged 75 years of age at baseline living in two districts in Vienna.…”
Section: Introductionmentioning
confidence: 99%
“…21 It is now clear that there are distinct EPC sub-populations with different phenotype and biological properties. 6 Cells progress from stem cell stage to the final mature cell of each single lineage, through successive progenitor cell stages, 23 and because uniform criteria to identify these cells are lacking, we followed the proposal outlined by Case et al 17 They suggested to use the CD45 neg / CD34 pos phenotype, because these cells form colonies of mature endothelial cells in a clonogenic in-vitro assay of endothelial cells. Therefore, probably these cells behave to a greater extent as true endothelial progenitors 19 and accordingly, CD45 neg /CD34 pos / CD144 pos cells form endothelial cells in culture.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of arterial ED was made when all the following criteria were fulfilled: (a) international index of erectile function (IIEF-5) score o21; 2 (b) cavernousal artery peak systolic velocity (PSV) o30 cm s À1 , 10 and 20 min after the intracavernousal injection of alprostadil (20 mg) by echo color Doppler; 3 and (c) acceleration time 4110 ms. 4 The diagnosis of MetS was made according to the ATP III criteria. 5 Patients were excluded if they (a) had severe hypogonadism (serum total testosterone levels o8 nmol l À1 (o231 ng dl À1 ) 6 and (b) smoked cigarettes. They underwent blood withdrawal (10 ml), for EPC and EMP measurements by flow cytometry.…”
Section: Patient Selectionmentioning
confidence: 99%
“…A close relationship between hypogonadism and central obesity, which is one of the criteria of metabolic syndrome, has been established. 30,31 From baseline to 1 year, ADT may increase fat mass by 9.4%-11.0%, 32,33 which consists of subcutaneous fat rather than visceral fat. Nevertheless, metabolic syndrome caused by ADT is to some extent distinct from the classic metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%